Cultural Influences on English Writing Styles: A Review of Studies on Indonesian ESL Learners - Sujarwati, Iis; Suningsih, Sri (Journal of Linguistics and Social Sciences, 2025)
This study investigates the cultural influences on English writing styles among Indonesian ESL learners. Through a systematic literature review, it identifies common characteristics, challenges, and themes in the writing of these students. The findings indicate that the influence of the Indonesian language and culture significantly impacts the coherence, organization, and syntax of English writing. Indonesian students tend to face difficulties in structuring their essays and utilizing the appropriate academic tone, often due to the transfer of their native language structures and cultural norms. This research emphasizes the need for culturally responsive teaching strategies in ESL classrooms to better support Indonesian learners. The findings highlight the importance of understanding cultural contexts when teaching writing skills, providing meaningful insights for educators looking to enhance their teaching practices in Indonesia